TINGKAT PENGETAHUAN MAHASISWA KESEHATAN DAN NON KESEHATAN TENTANG PENGGUNAAN ANTIBIOTIK DI UNIVERSITAS BAITURRAHMAH - Siska Ferilda; Eka Desnita; Alya Rohadi (STIKES Syedza Saintika Padang, 2024)
Antibiotic resistance has caused various problems and become a global threat to health. Excessiveand inappropriate use of antibiotics can cause the problem of bacterial resistance to antibiotics. Withthe occurrence of resistance problems, the potential for antibiotics to treat infections and diseaseswill decrease. Antibiotic resistance at this time is not widely known among the public. Based on dataobtained by the World Health Organization (WHO), there are a number of 12 countries includingIndonesia, accounting for 53.62% of people stop taking antibiotic drugs when they recover.Objective: This study aims to determine the level of knowledge of health and non-health studentsabout the use of antibiotic drugs at Baiturrahmah University Padang and to reduce the problem ofresistance. Method: Research design used with observational method with descriptive design. Result:Of the 152 respondents consisting of 73 health students and 79 non-healt h students, 118 studentswith good knowledge were obtained, consisting of 72 people (98.6%) health students and 46 people(58.2%) non-health students, 32 students with sufficient knowledge with 1 person (1.4%) healthstudents and 31 people (39.2%) other non-health students, Then there are 2 people (2.5%) non-healthstudents with less knowledge. There is an influence between education and gender on the level ofknowledge with Sig (0.00) < (0.05) values. Conclusion: The level of knowledge of health students isbetter than that of non-health students. And there are significant differences between health and non-health studentsKeywords: Resistance, Antibiotics, Knowledge of antibiotic